Heat-conducting gasket with low dielectric constant, low oil permeability and high heat conductivity and preparation method of heat-conducting gasket

By using linear bodies to synthesize low viscosity vinyl silicone oil and end-side hydrogen-containing silicone oil, combined with alumina and boron nitride of different particle sizes, a thermal conductivity gasket with low dielectric and low permeability oil and high thermal conductivity was prepared, which solved the problems of high dielectric constant and high oil permeability of existing thermal conductivity gaskets, and achieved both high thermal conductivity and low dielectric constant.

CN119552511APending Publication Date: 2025-03-04SHENZHEN DARBOND INTERFACE MATERIALS

Patent Information

Application Number
CN202411721128.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-04

AI Technical Summary

Technical Problem

There are problems with high dielectric constant and high oil permeability during use of existing thermal gaskets, which affect their thermal conductivity and the stability of components.

Method used

Low viscosity vinyl silicone oil synthesized by linear bodies and hydrogen-containing silicone oil with end-side hydrogen, combined with alumina and boron nitride of different particle sizes, low-dielectric and low-permeability oil and high-thermal conductivity thermal gaskets were prepared through high-speed dispersion and stirring.

Benefits of technology

The low dielectric constant (less than 4.0) and low oil permeability (less than 0.5%) of the thermal gasket are achieved, while the thermal conductivity coefficient (4.8-5.2W/m.K) is improved, which is suitable for the communication field in the 5G era.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005158061400000081
    Figure BDA0005158061400000081
  • Figure BDA0005158061400000091
    Figure BDA0005158061400000091
Patent Text Reader

Abstract

The invention relates to a heat-conducting gasket with low dielectric constant, low oil permeability and high heat conductivity and a preparation method thereof, and belongs to the technical field of heat-conducting gaskets. The heat-conducting gasket is prepared from the following components in parts by weight: 100 parts of vinyl silicone oil, 1-4 parts of hydrogen-containing silicone oil A, 8-14 parts of hydrogen-containing silicone oil B, 6-10 parts of a coupling agent, 6-10 parts of a dispersing agent, 0.2-2 parts of a catalyst, 0.4-4 parts of an inhibitor, 30-90 parts of aluminum oxide A, 130-230 parts of aluminum oxide B, 5-20 parts of aluminum oxide C, 80-180 parts of boron nitride A, 40-100 parts of boron nitride B and 40-100 parts of boron nitride C, the hardness of the prepared heat-conducting gasket with low dielectric constant, low oil permeability and high heat conductivity is 50-55 Shore OO, the heat conductivity coefficient is 4.8-5.2 W / m.K, the dielectric constant is smaller than 4.0, and the oil permeability rate is smaller than 0.5%; the method can be applied to the network communication field.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a low-dielectric, low-oil-permeability, high-thermal-conductivity thermally conductive pad and a preparation method thereof, belonging to the technical field of thermally conductive pads. Background Art

[0002] With the advent of the 5G era, in many occasions in the communication field, in order to reduce the impact of thermally conductive gaskets on the performance of antennas and transmission lines, not only high thermal conductivity requirements are placed on thermally conductive materials, but also the dielectric constant of thermally conductive materials is required to be as low as possible. In addition, during the use of thermally conductive gaskets, some small molecules and free silicone oil inside the gaskets will slowly precipitate and adsorb on electronic components, causing component failures, so low oil permeability performance has also received widespread attention. Chinese patent CN115491042B fills a large amount of high thermal conductivity powder in silicone gel, and adds part of polydimethylsiloxane (PDMS, also known as silicone oil) to adjust the softness and surface viscosity of the gasket to obtain a low-oil permeability and low-volatility thermally conductive gasket, but its thermal conductivity is only about 2.0W / mK; Chinese patent CN115304923B discloses a low-dielectric high-thermal conductive gasket and a preparation method thereof, but the patent does not explain its design and improvement of the oil permeability of the thermal pad. Summary of the invention

[0003] The object of the present invention is to provide a low-dielectric, low-oil-permeability, high-thermal-conductivity thermally conductive gasket and a preparation method thereof, so as to solve the technical problems existing in the prior art as described above.

[0004] To achieve the above objectives, the technical solutions adopted are:

[0005] One of the purposes of the present invention is to provide a low-dielectric, low-permeability oil and high-thermal-conductivity thermally conductive gasket, the components of which include, by weight: 100 parts of vinyl silicone oil, 1-4 parts of hydrogen-containing silicone oil A, 8-14 parts of hydrogen-containing silicone oil B, 6-10 parts of coupling agent, 6-10 parts of dispersant, 0.2-2 parts of catalyst, 0.4-4 parts of inhibitor, 30-90 parts of aluminum oxide A, 130-230 parts of aluminum oxide B, 5-20 parts of aluminum oxide C, 80-180 parts of boron nitride A, 40-100 parts of boron nitride B and 40-100 parts of boron nitride C.

[0006] On the basis of the above technical solution, the present invention can also be improved as follows:

[0007] Furthermore, the vinyl silicone oil is synthesized from a linear body, has a vinyl content of 0.1-0.4 mmoles / gm, and a viscosity of 100-800 cSt.

[0008] The beneficial effect of adopting the above further scheme is that vinyl silicone oil is used as the main silicone oil, which has a lower viscosity and can be well filled and dispersed in the thermal conductive powder. At the same time, vinyl silicone oil is synthesized from linear bodies and has a relatively low low-ring body content, which can effectively reduce oil production.

[0009] Furthermore, hydrogen-containing silicone oil A is a terminal hydrogen-containing silicone oil, whose active hydrogen content is 1.2-2.4 mmoles / gm and viscosity is 40-300 cSt; hydrogen-containing silicone oil B is a terminal hydrogen-containing silicone oil, whose active hydrogen content is 0.2-0.6 mmoles / gm and viscosity is 50-250 cSt.

[0010] The beneficial effect of adopting the above further scheme is that the terminal hydrogen-containing silicone oil can improve the crosslinking degree of the system. The terminal hydrogen-containing silicone oil acts as both a crosslinking agent and a chain extender in the system, thereby increasing the molecular weight of the vinyl silicone oil and further reducing oil production.

[0011] Furthermore, the coupling agent is a dodecylsilane coupling agent.

[0012] Furthermore, the dispersant is a hydroxyl-containing modified silicone oil, brand: DA30, manufacturer: Anbiya Special Silicone Co., Ltd.

[0013] Furthermore, the catalyst is a platinum catalyst with a platinum content of 3000 PPM.

[0014] Furthermore, the inhibitor is an alkynol inhibitor.

[0015] Furthermore, the aluminum oxide A is spherical aluminum oxide with a particle size of 5-15 um.

[0016] Furthermore, the aluminum oxide B is spherical aluminum oxide with a particle size of 100-150 um.

[0017] Furthermore, the aluminum oxide C is spherical aluminum oxide with a particle size of 0.5-10 um.

[0018] The beneficial effect of adopting the above further scheme is that by selecting alumina of different particle sizes to fill between the boron nitride, it acts as a connecting "bridge", which can not only solve the problem that the system is full of boron nitride and is difficult to fill, but also improve the thermal conductivity.

[0019] Furthermore, the boron nitride A is hexagonal boron nitride with a particle size of 140-240 um.

[0020] Furthermore, the boron nitride B is spherical boron nitride with a particle size of 40-100 um.

[0021] Furthermore, the boron nitride C is hexagonal boron nitride with a particle size of 20-80 um.

[0022] The beneficial effect of adopting the above further scheme is that the dielectric constant of boron nitride itself is lower than that of aluminum oxide, and the thermal conductivity is relatively high. By matching boron nitride of different particle sizes, the dielectric constant can be effectively reduced while ensuring the thermal conductivity.

[0023] The second object of the present invention is to provide a method for preparing the low-dielectric, low-oil-permeability, high-thermal-conductivity thermally conductive gasket, comprising the following steps:

[0024] (1) Add 100 parts of vinyl silicone oil, 1-4 parts of hydrogenated silicone oil A, 8-14 parts of hydrogenated silicone oil B, 6-10 parts of coupling agent, 6-10 parts of dispersant, 0.2-2 parts of catalyst, 0.4-4 parts of inhibitor, 80-180 parts of boron nitride A, 40-100 parts of boron nitride B and 40-100 parts of boron nitride C into a reaction container, and disperse at high speed for 40-80 seconds at a rotation speed of 600-900 rpm; then add 30-90 parts of aluminum oxide A, 130-230 parts of aluminum oxide B and 5-20 parts of aluminum oxide C, and disperse at high speed for 40-80 seconds at a rotation speed of 1000-1400 rpm; finally, stir at a rotation speed of 300-700 rpm for 20-60 seconds to obtain a mixture;

[0025] (2) Pressing the mixture obtained in step (1) into a sheet with a thickness of 1-2 mm, and baking it at 120-130° C. for 20-40 min to obtain a thermally conductive gasket with low dielectric, low oil permeability and high thermal conductivity.

[0026] Compared with the prior art, the technical solution provided by the present invention has the following beneficial effects:

[0027] 1. The present invention uses low-viscosity vinyl silicone oil synthesized from a linear body to control the low-ring body content in the vinyl silicone oil, and uses end-side hydrogen-containing silicone oil to improve the crosslinking degree of the system. The end-side hydrogen-containing silicone oil acts as both a crosslinking agent and a chain extender in the system, thereby increasing the molecular weight of the vinyl silicone oil and controlling the oil seepage of the thermally conductive gasket; by selecting alumina of different particle sizes to be filled between boron nitrides, it acts as a connecting "bridge", which can not only solve the problem that the system is full of boron nitride and is difficult to fill, but also improve thermal conductivity; the dielectric constant of boron nitride itself is lower than that of alumina, and the thermal conductivity is relatively high. By using boron nitride of different particle sizes, the dielectric constant can be effectively reduced while ensuring the thermal conductivity;

[0028] 2. The low-dielectric, low-oil-permeability, high-thermal-conductivity thermal gasket prepared by the present invention has a hardness of 50-55 Shore OO, a thermal conductivity of 4.8-5.2 W / mK, and a dielectric constant of less than 4.0. After the thermal gasket is compressed by 40%, the pressure is maintained and it is placed in a 70°C oven for baking for 168 hours, and the oil permeability is less than 0.5%. It can be used in the field of network communications. DETAILED DESCRIPTION

[0029] The principles and features of the present invention are described below in conjunction with examples. The examples are only used to explain the present invention and are not used to limit the scope of the present invention.

[0030] Example 1

[0031] A method for preparing a low-dielectric, low-oil-permeability, high-thermal-conductivity thermally conductive gasket, comprising the following steps:

[0032] (1) Add 100 parts of vinyl silicone oil (vinyl content 0.15 mmoles / gm, viscosity 550 cSt), 2 parts of hydrogenated silicone oil A (active hydrogen content 1.8 mmoles / gm, viscosity 100 cSt), 11 parts of hydrogenated silicone oil B (active hydrogen content 0.4 mmoles / gm, viscosity 100 cSt), 8 parts of dodecylsilane coupling agent, 7 parts of hydroxyl-modified silicone oil, 0.5 parts of platinum catalyst, 0.8 parts of ethynylcyclohexanol inhibitor, 120 parts of boron nitride A, 70 parts of boron nitride B and 70 parts of boron nitride C into a jar, and disperse at high speed for 40 seconds at a rotation speed of 900 rpm; then add 40 parts of aluminum oxide A, 150 parts of aluminum oxide B and 5 parts of aluminum oxide C, and disperse at high speed for 40 seconds at a rotation speed of 1400 rpm; finally, stir at a rotation speed of 300 rpm for 60 seconds to obtain a mixture;

[0033] (2) The mixture of step (1) is pressed into a sheet with a thickness of 1.5 mm, and baked at 125° C. for 30 min to obtain a thermally conductive gasket with low dielectric, low oil permeability and high thermal conductivity.

[0034] Example 2

[0035] A method for preparing a low-dielectric, low-oil-permeability, high-thermal-conductivity thermally conductive gasket, comprising the following steps:

[0036] (1) Add 100 parts of vinyl silicone oil (vinyl content 0.22 mmoles / gm, viscosity 250 cSt), 2.8 parts of hydrogenated silicone oil A (active hydrogen content 1.9 mmoles / gm, viscosity 50 cSt), 14 parts of hydrogenated silicone oil B (active hydrogen content 0.2 mmoles / gm, viscosity 250 cSt), 10 parts of dodecylsilane coupling agent, 10 parts of hydroxyl-modified silicone oil, 1 part of platinum catalyst, 1.5 parts of ethynylcyclohexanol inhibitor, 150 parts of boron nitride A, 80 parts of boron nitride B and 80 parts of boron nitride C into a jar, and disperse at high speed for 80 seconds at a rotation speed of 600 rpm; then add 50 parts of aluminum oxide A, 180 parts of aluminum oxide B and 15 parts of aluminum oxide C, and disperse at high speed for 80 seconds at a rotation speed of 1000 rpm; finally, stir at a rotation speed of 700 rpm for 30 seconds to obtain a mixture;

[0037] (2) The mixture of step (1) is pressed into a sheet with a thickness of 1.5 mm, and baked at 125° C. for 30 min to obtain a thermally conductive gasket with low dielectric, low oil permeability and high thermal conductivity.

[0038] Example 3

[0039] A method for preparing a low-dielectric, low-oil-permeability, high-thermal-conductivity thermally conductive gasket, comprising the following steps:

[0040] (1) Add 100 parts of vinyl silicone oil (vinyl content 0.22 mmoles / gm, viscosity 250 cSt), 2.8 parts of hydrogenated silicone oil A (active hydrogen content 1.9 mmoles / gm, viscosity 50 cSt), 14 parts of hydrogenated silicone oil B (active hydrogen content 0.2 mmoles / gm, viscosity 250 cSt), 6 parts of dodecylsilane coupling agent, 6 parts of hydroxyl-modified silicone oil, 1 part of platinum catalyst, 1.5 parts of ethynylcyclohexanol inhibitor, 180 parts of boron nitride A, 40 parts of boron nitride B and 40 parts of boron nitride C into a jar, and disperse at high speed for 80 seconds at a rotation speed of 600 rpm; then add 30 parts of aluminum oxide A, 200 parts of aluminum oxide B and 20 parts of aluminum oxide C, and disperse at high speed for 80 seconds at a rotation speed of 1000 rpm; finally, stir at a rotation speed of 700 rpm for 30 seconds to obtain a mixture;

[0041] (2) The mixture of step (1) is pressed into a sheet with a thickness of 1.5 mm, and baked at 125° C. for 30 min to obtain a thermally conductive gasket with low dielectric, low oil permeability and high thermal conductivity.

[0042] Comparative Example 1

[0043] (1) Add 100 parts of vinyl silicone oil (vinyl content 0.15 mmoles / gm, viscosity 550 cSt), 2 parts of hydrogenated silicone oil A (active hydrogen content 1.8 mmoles / gm, viscosity 100 cSt), 11 parts of hydrogenated silicone oil B (active hydrogen content 0.4 mmoles / gm, viscosity 100 cSt), 8 parts of dodecylsilane coupling agent, 7 parts of hydroxyl-modified silicone oil, 0.5 parts of platinum catalyst, 0.8 parts of ethynylcyclohexanol inhibitor, 70 parts of boron nitride A, 30 parts of boron nitride B and 35 parts of boron nitride C into a jar, and disperse at high speed for 40 seconds at a rotation speed of 900 rpm; then add 100 parts of aluminum oxide A, 240 parts of aluminum oxide B and 25 parts of aluminum oxide C, and disperse at high speed for 40 seconds at a rotation speed of 1400 rpm; finally, stir at a rotation speed of 300 rpm for 60 seconds to obtain a mixture;

[0044] (2) The mixture of step (1) was pressed into a sheet with a thickness of 1.5 mm, and baked at 125° C. for 30 min to obtain a thermally conductive pad.

[0045] Comparative Example 2

[0046] (1) Add 100 parts of vinyl silicone oil (vinyl content 0.8 mmoles / gm, viscosity 50 cSt), 2.5 parts of hydrogenated silicone oil A (active hydrogen content 3.8 mmoles / gm, viscosity 100 cSt), 7 parts of hydrogenated silicone oil B (active hydrogen content 0.8 mmoles / gm, viscosity 50 cSt), 10 parts of dodecylsilane coupling agent, 10 parts of hydroxyl-modified silicone oil, 1 part of platinum catalyst, 1.5 parts of ethynylcyclohexanol inhibitor, 150 parts of boron nitride A, 80 parts of boron nitride B and 80 parts of boron nitride C into a jar, and disperse at high speed for 80 seconds at a rotation speed of 600 rpm; then add 50 parts of aluminum oxide A, 180 parts of aluminum oxide B and 15 parts of aluminum oxide C, and disperse at high speed for 80 seconds at a rotation speed of 1000 rpm; finally, stir at a rotation speed of 700 rpm for 30 seconds to obtain a mixture;

[0047] (2) The mixture of step (1) was pressed into a sheet with a thickness of 1.5 mm, and baked at 125° C. for 30 min to obtain a thermally conductive pad.

[0048] Comparative Example 3

[0049] (1) Add 100 parts of vinyl silicone oil (vinyl content 0.15 mmoles / gm, viscosity 550 cSt), 2 parts of hydrogenated silicone oil A (active hydrogen content 1.8 mmoles / gm, viscosity 100 cSt), 11 parts of hydrogenated silicone oil B (active hydrogen content 0.4 mmoles / gm, viscosity 100 cSt), 8 parts of dodecylsilane coupling agent, 7 parts of hydroxyl-modified silicone oil, 0.5 parts of platinum catalyst, 0.8 parts of ethynyl cyclohexanol inhibitor, and boron nitride A 260 into a jar, and disperse at high speed for 40 seconds at a rotation speed of 900 rpm; then add 195 parts of aluminum oxide A, and disperse at high speed for 40 seconds at a rotation speed of 1400 rpm; finally, stir at a rotation speed of 300 rpm for 60 seconds to obtain a mixture;

[0050] (2) The mixture of step (1) was pressed into a sheet with a thickness of 1.5 mm, and baked at 125° C. for 30 min to obtain a thermally conductive pad.

[0051] Comparative Example 4

[0052] (1) Add 100 parts of vinyl silicone oil (vinyl content 0.15 mmoles / gm, viscosity 550 cSt), 2 parts of hydrogenated silicone oil A (active hydrogen content 1.8 mmoles / gm, viscosity 100 cSt), 11 parts of hydrogenated silicone oil B (active hydrogen content 0.4 mmoles / gm, viscosity 100 cSt), 8 parts of dodecylsilane coupling agent, 7 parts of hydroxyl-modified silicone oil, 0.5 parts of platinum catalyst, 0.8 parts of ethynyl cyclohexanol inhibitor, 120 parts of boron nitride A and 60 parts of boron nitride B into a jar, and disperse at high speed for 40 seconds at a rotation speed of 900 rpm; then add 60 parts of aluminum oxide A, and disperse at high speed for 40 seconds at a rotation speed of 1400 rpm; finally, stir at a rotation speed of 300 rpm for 60 seconds to obtain a mixture;

[0053] (2) The mixture of step (1) was pressed into a sheet with a thickness of 1.5 mm, and baked at 125° C. for 30 min to obtain a thermally conductive pad.

[0054] Comparative Example 5

[0055] (1) Add 100 parts of vinyl silicone oil (vinyl content 0.15 mmoles / gm, viscosity 550 cSt), 2 parts of hydrogenated silicone oil A (active hydrogen content 1.8 mmoles / gm, viscosity 100 cSt), 11 parts of hydrogenated silicone oil B (active hydrogen content 0.4 mmoles / gm, viscosity 100 cSt), 8 parts of dodecylsilane coupling agent, 7 parts of hydroxyl-modified silicone oil, 0.5 parts of platinum catalyst, 0.8 parts of ethynyl cyclohexanol inhibitor, 180 parts of boron nitride A, 50 parts of boron nitride B and 55 parts of boron nitride C into a jar, and disperse at high speed for 40 seconds at a rotation speed of 900 rpm; then stir at a rotation speed of 300 rpm for 60 seconds to obtain a mixture;

[0056] (2) The mixture of step (1) was pressed into a sheet with a thickness of 1.5 mm, and baked at 125° C. for 30 min to obtain a thermally conductive pad.

[0057] Comparative Example 6

[0058] (1) Adding 100 parts of vinyl silicone oil (vinyl content 0.15 mmoles / gm, viscosity 550 cSt), 2 parts of hydrogen-containing silicone oil A (active hydrogen content 1.8 mmoles / gm, viscosity 100 cSt), 11 parts of hydrogen-containing silicone oil B (active hydrogen content 0.4 mmoles / gm, viscosity 100 cSt), 8 parts of dodecylsilane coupling agent, 7 parts of hydroxyl-modified silicone oil, 0.5 parts of platinum catalyst, 0.8 parts of ethynyl cyclohexanol inhibitor, 300 parts of aluminum oxide A, 540 parts of aluminum oxide B and 80 parts of aluminum oxide C into a jar, dispersing at a high speed of 900 rpm for 40 seconds, and stirring at a rotation speed of 300 rpm for 60 seconds to obtain a mixture;

[0059] (2) The mixture of step (1) was pressed into a sheet with a thickness of 1.5 mm, and baked at 125° C. for 30 min to obtain a thermally conductive pad.

[0060] Comparative Example 7

[0061] (1) Add 100 parts of vinyl silicone oil (synthesized from a nonlinear body, with a vinyl content of 0.15 mmoles / gm and a viscosity of 550 cSt), 2 parts of hydrogenated silicone oil A (with an active hydrogen content of 1.8 mmoles / gm and a viscosity of 100 cSt), 11 parts of hydrogenated silicone oil B (with an active hydrogen content of 0.4 mmoles / gm and a viscosity of 100 cSt), 8 parts of dodecylsilane coupling agent, 7 parts of hydroxyl-modified silicone oil, 0.5 parts of platinum catalyst, 0.8 parts of ethynylcyclohexanol inhibitor, 120 parts of boron nitride A, 70 parts of boron nitride B and 70 parts of boron nitride C into a jar, and disperse at high speed for 40 seconds at a rotation speed of 900 rpm; then add 40 parts of aluminum oxide A, 150 parts of aluminum oxide B and 5 parts of aluminum oxide C, and disperse at high speed for 40 seconds at a rotation speed of 1400 rpm; finally, stir at a rotation speed of 300 rpm for 60 seconds to obtain a mixture;

[0062] (2) The mixture of step (1) is pressed into a sheet with a thickness of 1.5 mm, and baked at 125° C. for 30 min to obtain a thermally conductive gasket with low dielectric, low oil permeability and high thermal conductivity.

[0063] The brand of the hydroxyl-containing modified silicone oil of the above-mentioned dispersant is DA30, and the manufacturer is: Anbiya Special Silicone Co., Ltd.; the above-mentioned catalyst is a platinum catalyst with a platinum content of 3000PPM.

[0064] The thermally conductive pads obtained in Examples 1-3 and Comparative Examples 1-7 were subjected to performance tests:

[0065] (1) Hardness test: Tested according to ASTM D2240 standard;

[0066] (2) Thermal conductivity test: Tested in accordance with ISO22007-2.2 standard;

[0067] (3) Dielectric constant test: thickness 1.5 mm, test frequency 1 MHZ, tested in accordance with GB / T 1409-2006 standard;

[0068] (4) Oil permeability test: Sample size 25.4*25.4*1.5 mm was compressed by 40%, placed in a 70°C oven for 168 h, and the mass loss rate was calculated;

[0069] The test results are shown in Table 1 below:

[0070] Table 1 Performance test results of thermal conductive pads

[0071]

[0072]

[0073] It can be seen from the test results of Examples 1-3 and Comparative Examples 1-7 that the thermally conductive gaskets prepared in Examples 1-3 have a hardness of 50-55 Shore OO, a thermal conductivity of 4.8-5.2 W / mK, a dielectric constant of less than 4.0, and the gaskets are compressed 40% and baked in a 70°C oven for 168 hours, and the oil permeability is less than 0.5%; the thermally conductive gaskets prepared in Comparative Examples 1-7 have a hardness of 45-55 Shore OO, among which the thermal conductivity of Comparative Examples 1, 3, 4, 5, and 6 is relatively low, and the dielectric constant of Comparative Examples 1, 3, and 6 is also relatively high; the oil permeability of Comparative Examples 2 and 7 far exceeds 0.5%, reaching 0.891% and 0.722% respectively.

[0074] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A low dielectric, low oil permeability, high thermal conductivity thermal conductive pad, characterized in that: Calculated by weight, it includes: 100 parts of vinyl silicone oil, 1-4 parts of hydrogen-containing silicone oil A, 8-14 parts of hydrogen-containing silicone oil B, 6-10 parts of coupling agent, 6-10 parts of dispersant, 0.2-2 parts of catalyst, 0.4-4 parts of inhibitor, 30-90 parts of aluminum oxide A, 130-230 parts of aluminum oxide B, 5-20 parts of aluminum oxide C, 80-180 parts of boron nitride A, 40-100 parts of boron nitride B and 40-100 parts of boron nitride C.

2. The low-dielectric, low-penetration oil and high-thermal-conductivity thermally conductive pad according to claim 1, characterized in that: The vinyl silicone oil is synthesized from a linear body, has a vinyl content of 0.1-0.4 mmoles / gm, and a viscosity of 100-800 cSt.

3. The low-dielectric, low-penetration oil and high-thermal-conductivity thermally conductive pad according to claim 1, characterized in that: The hydrogen-containing silicone oil A is a terminal hydrogen-containing silicone oil with an active hydrogen content of 1.2-2.4 mmoles / gm and a viscosity of 40-300 cSt.

4. The low-dielectric, low-penetration oil and high-thermal-conductivity thermally conductive pad according to claim 1, characterized in that: The hydrogen-containing silicone oil B is a hydrogen-terminated hydrogen-containing silicone oil with an active hydrogen content of 0.2-0.6 mmoles / gm and a viscosity of 50-250 cSt.

5. The low-dielectric, low-penetration oil and high-thermal-conductivity thermally conductive pad according to claim 1, characterized in that: The coupling agent is a dodecylsilane coupling agent; the dispersant is a hydroxyl-containing modified silicone oil; the catalyst is a platinum catalyst; and the inhibitor is an acetyl alcohol inhibitor.

6. The low-dielectric, low-penetration oil and high-thermal-conductivity thermally conductive gasket according to claim 1, characterized in that: The aluminum oxide A is spherical aluminum oxide with a particle size of 5-15 um, the aluminum oxide B is spherical aluminum oxide with a particle size of 100-150 um, and the aluminum oxide C is quasi-spherical aluminum oxide with a particle size of 0.5-10 um.

7. The low-dielectric, low-penetration oil and high-thermal-conductivity thermally conductive gasket according to claim 1, characterized in that: The boron nitride A is hexagonal boron nitride with a particle size of 140-240 um, the boron nitride B is spherical boron nitride with a particle size of 40-100 um, and the boron nitride C is hexagonal boron nitride with a particle size of 20-80 um.

8. A method for preparing a low-dielectric, low-penetration oil and high-thermal-conductivity thermally conductive gasket as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: (1) adding 100 parts of vinyl silicone oil, 1-4 parts of hydrogenated silicone oil A, 8-14 parts of hydrogenated silicone oil B, 6-10 parts of coupling agent, 6-10 parts of dispersant, 0.2-2 parts of catalyst, 0.4-4 parts of inhibitor, 80-180 parts of boron nitride A, 40-100 parts of boron nitride B and 40-100 parts of boron nitride C into a reaction container, dispersing at high speed for 40-80 seconds at a rotation speed of 600-900 rpm; then adding 30-90 parts of aluminum oxide A, 130-230 parts of aluminum oxide B and 5-20 parts of aluminum oxide C, dispersing at high speed for 40-80 seconds at a rotation speed of 1000-1400 rpm; finally stirring at a rotation speed of 300-700 rpm for 20-60 seconds to obtain a mixture; (2) Pressing the mixture obtained in step (1) into a sheet with a thickness of 1-2 mm, and baking it at 120-130° C. for 20-40 min to obtain a thermally conductive gasket with low dielectric, low oil permeability and high thermal conductivity.

Citation Information

Patent Citations

  • A low dielectric and high thermal conductivity gasket and preparation method thereof

    CN115304923B

  • A thermally conductive pad with low oil permeability and low volatility and its preparation method.

    CN115491042B

Cited By

  • Preparation method of heat-conducting gasket on intelligent communication terminal, heat-conducting gasket and application of heat-conducting gasket

    CN121699229A